2004
DOI: 10.1111/j.1525-1497.2004.30420.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with the outpatient encounter

Abstract: OBJECTIVE:To compare patients' and physicians' visit-specific satisfaction in an internal medicine outpatient setting, and to explain their respective views. DESIGN:Patients' and physicians' background characteristics were assessed prior to outpatient encounters. Immediately after the encounter, both patients and physicians completed a questionnaire assessing satisfaction with the visit. SETTING:The outpatient division of an academic teaching hospital. PARTICIPANTS:Thirty residents and specialists in general i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(60 citation statements)
references
References 45 publications
5
53
1
1
Order By: Relevance
“…The questionnaire is developed and tested in the home situation in the Netherlands. Physician satisfaction turned out to be substantially lower than patient satisfaction, both at item level and at overall satisfaction level [39]. This finding is consistent with other patient satisfaction studies [40,41].…”
Section: Methodssupporting
confidence: 78%
“…The questionnaire is developed and tested in the home situation in the Netherlands. Physician satisfaction turned out to be substantially lower than patient satisfaction, both at item level and at overall satisfaction level [39]. This finding is consistent with other patient satisfaction studies [40,41].…”
Section: Methodssupporting
confidence: 78%
“…Care providers might not be aware of this need for information, as it was shown that provision of information was valued more by patients than by physicians. 18 Other studies have also highlighted the psychosocial care need found in our study. Lifestyle and emotional issues were not addressed by GPs and specialists for over 75% of patients in the United Kingdom, Canada and the United States, 10 and the prevalence of depression in persons with SCI of approximately 20% was higher than that in the average population (10%).…”
Section: Care Receivedsupporting
confidence: 67%
“…Qualitatively derived themes guided questionnaire development. Validated patient satisfaction surveys [24][25][26][27][28] were searched for items relating to these themes. Items relating to overall patient satisfaction were also extracted from the Press Ganey survey.…”
Section: Methodsmentioning
confidence: 99%
“…Interview themes were compared to existing literature about patient satisfaction and observer presence in consultations. Items from validated questionnaires were used [24][25][26][27][28] to generate a final list of 22 items (by author consensus) that pertained to the qualitatively derived themes, which were selected for inclusion, some of which had negative valence to other items ('I felt that I had the doctor's full attention' vs 'I felt that the doctor was distracted') to test for reliability. Five items were unaltered Press Ganey overall patient satisfaction questions.…”
Section: Questionnairementioning
confidence: 99%